Gestão patrimonial: um estudo sobre o controle de material permanente na Universidade Federal do Maranhão - Figueredo, Francisco Carlos Marques (2015)
This study focuses on the financial management of movable property in the Center of Biological and Health Sciences (CCBS) of the Federal University of Maranhão (UFMA), according to Torres Junior (2003) the wealth management is to plan, organize, control, ensure, conserve and promote the best use of permanent materials available in the organization. This research aims to examine the criteria adopted in the processes of acquisition and disposal of permanent materials. Therefore, we discussed knowledge of the asset management regulations applied to heritage resources, information technology in public administration and sustainable logistics plan. This knowledge is grounded in the views of authors such as Davemport (1994), Moresi (2000), Francischini and Gurgel (2002), Cross (2003), Coutinho (2004), Silva, Ribeiro and Rodrigues (2004), Martins et AL (2007 ), Oliveira (2007), Pozo (2007), Bobsin and Lobler (2008), Carvalho Filho (2008), Gomes and Tortato (2010), Santos (2012), Meirelles (2012), Vinhais, Manso and Silva (2012) , Meza and Fijor (2013), among others. This case study is descriptive, exploratory and qualitative. Two questionnaires were applied to servers with the academic departments of the CCBS and Registration Division Asset respectively, and proceeded the analysis of existing documentation in the archives of the institution on the financial management which enabled the collection of data that were subsequently analyzed. The results show that the studied unit has been unable to efficiently manage its property, not given the precepts both the current legislation, as the organs of internal and external control. In one of the goals are some proposals for improvements, such as preparation of a manual of procedures based on current legislation, promote seminars on asset management.